2003
DOI: 10.1021/jo0346398
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Orthogonally Protected Lanthionines

Abstract: Synthetic approaches to the lantibiotics, a family of thioether-bridged antimicrobial peptides, require flexible synthetic routes to a variety of orthogonally protected derivatives of lanthionine 1. The most direct approaches to lanthionine involve the reaction of cysteine with an alanyl beta-cation equivalent. Several possibilities exist for the alanyl beta-cation equivalent, including direct activation of serine under Mitsunobu conditions: however, the low reactivity of sulfur nucleophiles in the Mitsunobu r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 30 publications
0
39
1
Order By: Relevance
“…demonstrated that the interpretations made by Dugave and Ménez and by Swali et al. of the reactions of ( R )‐ 103 with ( R )‐ 105 or ( S )‐ 109 had to be reassessed (Scheme and Scheme ) . Indeed, when the synthesis of β‐iodoalanine 109 is done through the mesylate with the Dugave's iodination method, 2D‐NMR shows a mixture with an isomeric form …”
Section: Chemical Synthesis Of Protected Lanthioninescontrasting
confidence: 77%
See 2 more Smart Citations
“…demonstrated that the interpretations made by Dugave and Ménez and by Swali et al. of the reactions of ( R )‐ 103 with ( R )‐ 105 or ( S )‐ 109 had to be reassessed (Scheme and Scheme ) . Indeed, when the synthesis of β‐iodoalanine 109 is done through the mesylate with the Dugave's iodination method, 2D‐NMR shows a mixture with an isomeric form …”
Section: Chemical Synthesis Of Protected Lanthioninescontrasting
confidence: 77%
“…Moreover, Mohd Mustapa et al. described that the HSQC spectrum of the β‐iodoalanine prepared from the mesylate ( R )‐ 118 corresponds to a mixture of enantiomers of α‐iodo‐β‐alanine ( R / S )‐ 119 , contaminated by the desired β‐iodo‐α‐alanine ( S )‐ 109 as the minor product (Scheme ) …”
Section: Chemical Synthesis Of Protected Lanthioninesmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to overcome the troublesome operation required for product isolation due to the presence of cysteine and cystine [24] and evaluate the efficiency of the reaction on the basis of isolated product yield, the photoinduced reaction of allyl a-C-galactoside 1 a with N-Fmoc cysteine tert-butyl ester (4) [25] was performed under the optimized conditions of run 4 in Table 1. From this reaction, the galactosyl amino ester 5 a was readily isolated by chromatography in excellent yield (92 %) ( Table 2).…”
mentioning
confidence: 99%
“…The amino groups were protected as azides, and the alcohols were subsequently converted into the iodides via the mesylates with sodium iodide in acceptable yields and in agreement with previous synthesis of analogues. [24,25] The imidazoles and alkyl iodides were employed in the synthesis of four different imidazolium salts as shown in Scheme 3. S N 2 iodide displacements in compounds 2 by the imidazoles 1 generated the imidazolium iodides in moderate yields (40-42 %) after purification on silica gel.…”
Section: Preparation Of Chiral Imidazolium Building Blocks As Precursmentioning
confidence: 99%